Time perspectives on intermodal transport of consolidated cargo - Sommar, Robert; Woxenius, Johan (European Journal of Transport and Infrastructure Research, 2007)
Intermodal road-rail freight transport is often argued to have certain cost and time handicaps against all-road transport. Based on theory defining the elements transport time, order time, timing, punctuality and frequency, literature on modal choice is surveyed. With few exceptions, transport time and punctuality is top ranked, while frequency and timing is regarded as less important by respondents. Timing is excluded in some studies and order time is not found. The time elements are also used for comparing the characteristics of intermodal transport and all-road transport. Particular attention is paid to the preconditions for using intermodal transport as part of consolidation networks with subsequent terminal handlings. Since time aspects in transportation are highly contextual, the analysis is deepened within the framework of a case study focusing Schenker’s domestic transport services in Sweden. Schenker’s time requirements are matched against the times CargoNet, their main supplier of intermodal terminal-to-terminal services, can offer. It is concluded that correspondence of the transport time between the consolidation network and the intermodal network are in fact not a strong prerequisite to use intermodal transport, although correspondence of departure and arrival times is significantly higher for the intermodal relations regularly used by the logistics service provider. Regarding timing, adjusting departure and arrival times by one hour will not increase the competitiveness for the consolidated cargo significantly, more profound adjustments are required. The order time of the intermodal freight transport service is not well suited to consolidated cargo due to volume information unavailability. The consolidated cargo schedule is sensitive for rather small deviations in punctuality.